African Americans with pancreatic ductal adenocarcinoma exhibit gender differences in Kaiso expression. Issue 2 (1st October 2016) - Jones, Jacqueline; Mukherjee, Angana; Karanam, Balasubramanyam; Davis, Melissa; Jaynes, Jesse; Reams, R. Renee; Dean-Colomb, Windy; Yates, Clayton
Highlights: Kaiso expression is elevated in High Grade Pancreatic Tumors. Males with Pancreatic Cancer have significantly increased expression of cytoplasmic and nuclear Kaiso. Kaiso and ZEB1 correlate with loss of E-cadherin expression. Abstract: Kaiso, a bi-modal transcription factor, regulates gene expression, and is elevated in breast, prostate, and colon cancers. Depletion of Kaiso in other cancer types leads to a reduction in markers for the epithelial–mesenchymal transition (EMT) (Jones et al., 2014), however its clinical implications in pancreatic ductal adenocarcinoma (PDCA) have not been widely explored. PDCA is rarely detected at an early stage but is characterized by rapid progression and invasiveness. We now report the significance of the subcellular localization of Kaiso in PDCAs from African Americans. Kaiso expression is higher in the cytoplasm of invasive and metastatic pancreatic cancers. In males, cytoplasmic expression of Kaiso correlates with cancer grade and lymph node positivity. In male and female patients, cytoplasmic Kaiso expression correlates with invasiveness. Also, nuclear expression of Kaiso increases with increased invasiveness and lymph node positivity. Further, analysis of the largest PDCA dataset available on ONCOMINE shows that as Kaiso increases, there is an overall increase in Zeb1, which is the inverse for E-cadherin. Hence, these findings suggest a role for Kaiso in the progression of PDCAs, involving the EMT markers, E-cadherin and Zeb1.